Réponses

2013-05-01T15:36:20+02:00

1) -3(x+5)(x-1) = 0

 

-3x -15 = 0                                                              x-1 = 0

-3x        = 15                                                                  x = 1

    x        = 15/-3  

    x        = -5

S = {-5;1}

 

x                               -∞            -5                       1                                 +∞

____________________________________________________

signe de

-3(x+5)                           -                     -              O             +

______________________________________________________

signe de 

(x-1)                                -        O             +                          +

_____________________________________________________

signe de 

 -3(x+5)(x-1)                  +        O            -            O             +